STUDENTS' INDIVIDUAL MOTIVE AND ACADEMIC PERFORMANCES IN HIGHER EDUCATION - Yohan Yohan (Scientia: Jurnal Hasil Penelitian, 2016)
This article is a narrative study which investigated student‟s individual motives to be engaged in higher education, and then to know their difficulties in academic demands in higher education programs and how they cope with the difficulties. Besides, this study also scrutinised the gaps in their academic attitudes towards their academic performances during they were engaged in a college stay. Unstructured–interview conducted to two classes which were purposively grouped by research-based that consisted of 20 students in each group in the forms of focused–group discussion and a deep-interview was given to 10 students. The researcher also used observation for particular occurrences. The findings showed that most of the students‟ purposes to be engaged in a college stay were only universal; becoming better individuals, creating pride and happiness for their parents, the pursuit of knowledge for some skills and interests, and improving jobs and financial careers.Moreover, then, their difficulties in college life correspond to financial, social-campus life, educational, and personal constraints. Besides, their gaps in academic performances consisted of an inappropriate way of behaving and respecting their lecturers, procrastination, wasting time, critical thinking disability, exams unpreparedness, lack of self-motivation drives, comprehension disability, academic anxiety, time management, academic tasks negligence, and burden requirements in the student organisation. In conclusion, profoundly and broadly reformulating their missions for studying in higher education, employing their approaches to scholarly communication and using other alternative strategies for the constraints should be their primary concern in achieving a better academic success.